Rice Premature Leaf Senescence 2, Encoding a Glycosyltransferase (GT), Is Involved in Leaf Senescence - Wang, Min; Zhang, Tao; Peng, Hao; Luo, Sheng; Tan, Juejie; Jiang, Kaifeng; Heng, Yueqin; Zhang, Xin; Guo, Xiuping; Zheng, Jiakui; Cheng, Zhijun (Frontiers in Plant Science, 2018)
Premature leaf senescence (PLS), which has a significant impact on yield, is caused by various underlying mechanisms. Glycosyltransferases, which function in glycosyl transfer from activated nucleotides to aglycones, are involved in diverse biological processes, but their roles in rice leaf senescence remain elusive. Here, we isolated and characterized a leaf senescence-related gene from the Premature Leaf Senescent mutant (pls2). The mutant phenotype began with leaf yellowing at tillering and resulted in PLS during the reproductive stage. Leaf senescence was associated with an increase in hydrogen peroxide (H2O2) content accompanied with pronounced decreases in net photosynthetic rate, stomatal conductance, and transpiration rate. Map-based cloning revealed that a mutation in LOC_Os03g15840 (PLS2), a putative glycosyltransferase- encoding gene, was responsible for the defective phenotype. PLS2 expression was detected in all tissues surveyed, but predominantly in leaf mesophyll cells. Subcellular localization of the PLS2 was in the endoplasmic reticulum. The pls2 mutant accumulated higher levels of sucrose together with decreased expression of sucrose metabolizing genes compared with wild type. These data suggested that the PLS2 allele is essential for normal leaf senescence and its mutation resulted in PLS.